H3K9 demethylases IBM1 and JMJ27 are required for male meiosis in Arabidopsis thaliana. Issue 6 (27th June 2022) - Cheng, Jinping; Xu, Linhao; Bergér, Valentin; Bruckmann, Astrid; Yang, Chao; Schubert, Veit; Grasser, Klaus D.; Schnittger, Arp; Zheng, Binglian; Jiang, Hua
Summary: Dimethylation of histone H3 lysine 9 (H3K9me2), a crucial modification for heterochromatin formation and transcriptional silencing, is essential for proper meiotic prophase progression in mammals. We analyzed meiotic defects and generated genome‐wide profiles of H3K9me2 and transcriptomes for the mutants of H3K9 demethylases. Moreover, we also identified proteins interacting with H3K9 demethylases. H3K9me2 is usually found at transposable elements and repetitive sequences but is absent from the bodies of protein‐coding genes. In this study, we show that the Arabidopsis thaliana H3K9 demethylases IBM1 and JMJ27 cooperatively regulate crossover formation and chromosome segregation. They protect thousands of protein‐coding genes from ectopic H3K9me2, including genes essential for meiotic prophase progression. In addition to removing H3K9me2, IBM1 and JMJ27 interact with the Precocious Dissociation of Sisters 5 (PDS5) cohesin complex cofactors. The pds5 mutant shared similar transcriptional alterations with ibm1 jmj27, including meiosis‐essential genes, yet without affecting H3K9me2 levels. Hence, PDS5s, together with IBM1 and JMJ27, regulate male meiosis and gene expression independently of H3K9 demethylation. These findings uncover a novel role of H3K9me2 removal in meiosis and a new function of H3K9 demethylases and cohesin cofactors in meiotic transcriptional regulation.